Une guerre dans la guerre : Yougoslavie 1941-1945 - Djilas, Milovan; Vierne, Béatrice; Christitch, Kosta (Paris : Editions Robert Laffont, 1979)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Tito, Josip Broz; revolutie; burgeroorlogen; Joegoslavië